Evaluasi Keamanan Informasi pada Perusahaan Skincare DNY Berdasarkan Indeks Keamanan Informasi (KAMI) ISO/IEC 27001:2013 - Pratomo, Ozilla Junior; Al Huraibi, Mohammad Ulil Azmi; Ridwan, Mujib (INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS : Journal of Information System; Vol 10 No 2 (2025): INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS (Desember 2025)DO - 10.51211/isbi.v10i2.3670, 2025)
The implementation of an information security system at DNY Skincare Company using the KAMI index in accordance with ISO/IEC 27001 standards shows satisfactory results. This study evaluates the maturity level of information security governance, asset management, and the risks faced by the company. The evaluation results indicate that the company has effectively implemented information security policies, particularly in personal data protection. However, there are several areas that still need improvement, such as data validity and risk management. The KAMI index provides insights into the company's readiness to face information security challenges. These findings emphasize the importance of continuous improvement to ensure optimal protection of consumer information and compliance with international standards.